2016
DOI: 10.7883/yoken.jjid.2014.567
|View full text |Cite
|
Sign up to set email alerts
|

Using an Autoregressive Integrated Moving Average Model to Predict the Incidence of Hemorrhagic Fever with Renal Syndrome in Zibo, China, 2004–2014

Abstract: SUMMARY: Hemorrhagic fever with renal syndrome (HFRS) is highly endemic in mainland China, where human cases account for 90z of the total global cases. Zibo City is one of the most seriously affected areas in Shandong Province, China. Therefore, there is an urgent need for monitoring and predicting HFRS incidence in Zibo to make the control of HFRS more effective. In this study, we constructed an autoregressive integrated moving average (ARIMA) model for monthly HFRS incidence in Zibo from 2004 to 2013. The AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…It is very useful in modeling temporal dependence structure of a time series. At present, this method has been widely used in the prediction of infectious diseases, and has achieved successful prediction results, for instance, Tian C W et al [4] forecasted monthly cases of hand-foot-mouth disease successfully in China; Wang T et al [5] suggested that ARIMA(3,1,1)(2,1,1) 12 model was reliable with a high validity, which could be used to predict hemorrhagic fever with renal syndrome incidence in Zibo; Myriam Gharbil et al [6] predicted the dengue incidence in Guadeloupe based on time series analysis; López-Montenegro LE [7] predicted dengue cases in Colombia from 2018 to 2022 based on Auto-Regressive Integrated Moving Average (ARIMA) model; Zheng Y-L et al [8] and Liao Z [9] forcasted TB incidence successfully using SARIMA model, etc. [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is very useful in modeling temporal dependence structure of a time series. At present, this method has been widely used in the prediction of infectious diseases, and has achieved successful prediction results, for instance, Tian C W et al [4] forecasted monthly cases of hand-foot-mouth disease successfully in China; Wang T et al [5] suggested that ARIMA(3,1,1)(2,1,1) 12 model was reliable with a high validity, which could be used to predict hemorrhagic fever with renal syndrome incidence in Zibo; Myriam Gharbil et al [6] predicted the dengue incidence in Guadeloupe based on time series analysis; López-Montenegro LE [7] predicted dengue cases in Colombia from 2018 to 2022 based on Auto-Regressive Integrated Moving Average (ARIMA) model; Zheng Y-L et al [8] and Liao Z [9] forcasted TB incidence successfully using SARIMA model, etc. [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In China, TB is categorised to class B notifiable diseases, and the incidence ranks second among all of the class B notifiable diseases [3]. The seasonal autoregressive integrated moving average (SARIMA) model is widely used to predict the incidence of infectious diseases [4][5][6][7], and also adopted as the main method in TB prediction around the world [8]. However, TB seasonality in China was mainly reported in local areas and the recent nationwide trend has not been reported [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…At this time, the existing mathematical models, specifically the autoregressive integrated moving average (ARIMA) model that is widely used to predict incidence of infectious diseases, [13][14][15] are based on linear assumptions. Moreover, the generalized regression neural network (GRNN) model, which is generally used to analyze the nonlinear data sets, could also be used.…”
Section: Introductionmentioning
confidence: 99%